Mealworm (Tenebrio Molitor) Oil And Its Potential As Biodiesel Feedstock Optimised By Response Surface Methodology - Siow, Hao Sen (2023)
The thriving global energy demand has driven the need for potential alternatives to replace the commercially available oil resources. One of the alternatives is insects, which are known to have high-fat content depending on their behaviour, feeding patterns, and worldwide availability. This study strives to discover the potential of mealworm (Tenebrio molitor) to be a stand-in bioenergy resource and converting it into biodiesel by optimising the process using response surface methodology (RSM). Mealworm had a high oil content of 37.54 ± 0.78% with a high free fatty acid (FFA) content of 10.84 ± 0.005%. The primary fatty acids of mealworm oil were oleic acid (30.37%), linoleic acid (25.07%), and palmitic acid (19.54%). The pyrolysis of mealworm oil was done from room temperature to 750°C at a heating rate of 10°C per minute under a nitrogen gas atmosphere and it decomposed almost completely after 470°C. An acid-catalysed esterification pre-treatment was conducted to reduce the high level of FFA content to a range below 1% using the optimum parameter of 5.8% w/w sulphuric acid as catalyst, 24:1 methanol-to-oil ratio, 174 minutes reaction time at 74°C to be favourable for alkali-catalysed transesterification to take place and convert the triglycerides in the oil into fatty acid methyl esters (FAME).